The impact of supply chain social responsibility on sustainable performance. (20th January 2023) - Yu, Yubing; Xu, Jiawei; Huo, Baofeng; Zhang, Justin Zuopeng; Cao, Yanhong
Abstract: To achieve sustainable development and cope with growing socioenvironmental pressure, manufacturing companies are becoming increasingly committed to fulfilling their social responsibilities along the entire supply chain. However, it is still unclear whether fulfilling supply chain social responsibility can improve sustainable performance. On the basis of stakeholder theory and using structural equation modeling (SEM) and fuzzy set qualitative comparative analysis (fsQCA), this study explores the complex relationship between supply chain social responsibility and sustainable performance using data collected from 209 Chinese manufacturing companies. The SEM findings show that supply chain social responsibility can improve sustainable performance, while the fsQCA results suggest that the impact of supply chain social responsibility on sustainable performance depends on fulfillment methods. In particular, three supply chain social responsibility patterns can help achieve highly sustainable performance. However, these patterns significantly impact economic, environmental, and social performance in different ways. Our empirical study provides theoretical and practical guidance for companies to fulfill their supply chain social responsibilities.